Student loan debt use and awareness: a social learning approach - Stutz, Kristen E. (Kansas State University, 2019)
Earning a bachelor’s degree is still a wise economic decision as college graduates have lower unemployment rates and higher weekly income averages than their high school graduate counterparts (Torpey, 2018). However, when students must go into debt to finance this opportunity, the clarity of these benefits becomes economically, personally, and socially more convoluted, and the question arises whether college students have sufficient financial literacy and social capital to make the complex financial decisions related to college financing. While studies have explored students’ perception of their debt after they have graduated (Baum & O’Malley, 2003; Baum & Saunders, 1998), it can also be useful to explore students’ perceptions of debt while in school. Using a social learning theoretical lens and a focus on first-generation college students, this study attempts to explore how students use and view their student loan debt at the point-in-time that they are making their student loan debt level decision. To achieve this, three empirical models were developed to explore relationships between environmental and internal factors and student loan use, balance, and balance awareness. Results generally indicate that both subjective and objective financial need variables and financial anxiety consistently predicted student loan behaviors. Implications for student loan educators, front line student service providers, and policymakers are discussed.
Keywords: Student loan; Student debt; Debt awareness; First-generation college student